Makna Tanda Kekerasan Seksual terhadap Perempuan - Salsabila Dhiyaa Syahira; Alex Sobur (UNISBA Press, 2023)
Abstract. Cases of sexual violence in Indonesia occupy the highest position with a total of 11,236 cases recorded, in which the majority of victims are women with various statuses. Film is a form of mass communication that is considered easy in disseminating information to the public, especially regarding the issue of sexual violence. One of the films that discusses the issue of sexual violence is the film Photocopier by Wregas Bhanuteja. The meaning of signs of sexual violence against women can be found through scenes and dialogues from the film Photocopier in 12 scenes. In this film, it is told that there is a female student named Suryani or Sur who has been a victim of sexual violence which resulted in her scholarship being revoked. This film is the only Indonesian film and the most watched non-English film in the world and has been watched for 6.92 million hours globally in one week. The purpose of this research is to see the meaning of the sign of sexual violence against women contained in the film, which will then take some of the necessary scene cuts. This study was compiled using qualitative methods with Roland Barthes' semiotic analysis which focuses on three levels of meaning. First, the meaning of the denotation which shows the meaning of the sign of sexual violence against women, namely when Amin was found to have traded female student content that was sexual in nature. Second, the connotative meaning which explains that acts of sexual violence experienced by women are not a serious matter and are instead taken for granted. Finally, the meaning of the myth that emerges from this film is that women who wear revealing clothes are more vulnerable to becoming victims of sexual violence than other people around them. Abstrak. Kasus kekerasan seksual di Indonesia menempati posisi tertinggi dengan total 11.236 kasus yang tercatat, di mana sebagian besar korbannya adalah seorang perempuan dengan berbagai status. Film merupakan salah satu bentuk komunikasi massa yang dianggap mudah dalam menyebarkan informasi kepada khalayak, khususnya mengenai isu kekerasan seksual. Salah satu film yang membahas mengenai isu kekerasan seksual adalah film Penyalin Cahaya karya Wregas Bhanuteja. Makna tanda kekerasan seksual terhadap perempuan dapat ditemukan melalui scene-scene maupun dialog dari film Penyalin Cahaya sebanyak 12 scene. Dalam film ini, diceritakan ada salah seorang mahasiswi bernama Suryani atau Sur yang telah menjadi korban kekerasan seksual sehingga mengakibatkan beasiswanya dicabut. Film ini menjadi satu-satunya film Indonesia dan film nonInggris yang paling banyak ditonton di dunia dan telah ditonton selama 6,92 juta jam secara global dalam jangka waktu satu minggu. Tujuan dari penelitian ini adalah untuk melihat makna tanda kekerasan seksual terhadap perempuan yang terkandung dalam film yang kemudian akan diambil beberapa potongan adegan yang dibutuhkan. Penelitian ini disusun dengan menggunakan metode kualitatif dengan analisis semiotika Roland Barthes yang berfokus pada tiga level pemaknaan. Pertama, makna denotasi yang memperlihatkan makna tanda kekerasan seksual terhadap perempuan yaitu ketika Amin yang didapati telah memperjualbelikan konten mahasiswi yang berbau seksual. Kedua, makna konotasi yang menjelaskan bahwa tindak kekerasan seksual yang dialami oleh perempuan bukanlah suatu hal yang serius dan justru dianggap remeh. Terakhir, makna mitos yang muncul dari film ini yaitu mengenai perempuan yang mengenakan pakaian terbuka lebih rentan menjadi korban tindak kekerasan seksual dari orang lain disekitarnya.